Influence of Rearing Photoperiod and Age and Mode of Transfer to Final Photoperiod on Performance in Egg-Type Pullets - Lewis, Peter D.; Caston, Linda; Leeson, Steve (International Journal of Poultry Science, 2008)
Lohmann White pullets were reared on 6, 9 or 12-h photoperiods and abruptly transferred to 14 h at 16 or 18 weeks or in a series of increments from 16 weeks. Body weight at and feed intake to 16 and 18 weeks increased with photoperiod. There were no interactions of rearing photoperiod with photo stimulation age/mode for any performance parameter. Sexual maturity was advanced by rearing on the longer photoperiods and by photostimulating at 16 rather than 18 weeks. Birds reared on 9 or 12 h laid significantly more eggs than 6-h birds, but neither age nor mode of photostimulation significantly affected egg production. Egg numbers were significantly correlated with age at sexual maturity. Mean egg weight was significantly heavier for pullets reared on 9 or 12 h than on 6 h, despite the former’s earlier maturity and for birds photostimulated at 18 rather 16 weeks. Mean daily feed in the laying period was not significantly affected by rearing photoperiod or photostimulation age/method and shell quality, though significantly reduced by rearing on longer photoperiods, was minimally affected by the lighting regimens in practical terms. The trend towards rearing egg-type pullets on longer photoperiods was vindicated, irrespective of photostimulation age or method.